Germany : Financial Sector Assessment Program-Detailed Assessment of Observance on the Basel Core Principles for Effective Banking Supervision. (IMF Staff Country Reports; Country Report ;, 2016)
This paper provides assessment of the current state of the implementation of the Basel Core Principles for Effective Banking Supervision in Germany. Since the last Financial Sector Assessment Program (FSAP), German banking supervision has undergone profound changes, with approval of the Capital Requirements Regulation (CRR) and Directive (CRD IV), establishment of the European Banking Authority,aand creation of the Single Supervisory Mechanism. The last FSAP (2011) found banking system supervision to be generally sound with some areas in need of improvement-although some of these issues have been addressed, others remain. While supervisory landscape in Germany evolves, it is crucial that supervisors communicate their expectations to banks and develop guidelines and regulations that can be used to substantiate enforceable measures.